2020
DOI: 10.1186/s13020-020-00305-1
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin and 4-hydroxytamoxifen synergistically inhibit the proliferation of breast cancer cells through activating apoptosis signaling pathway in vitro and in vivo

Abstract: Background: Tamoxifen (TAM) is a cell type-specific anti-estrogen and is applied to improve the survival of patients with estrogen receptor positive (ER +) breast cancer. However, long-term TAM use can induce serious drug resistance, leading to breast cancer recurrence and death in patients. Further, it is almost useless among patients with estrogen receptor negative (ER −) breast cancer. Shikonin (SK) is a natural product broadly explored in cancer therapy. Some studies have demonstrated the combined treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…MDA-MB-231 demonstrated an antagonistic response with the compound combination. Lin et al, also observed some antagonistic responses when treating this cell line with shikonin and 4-OHT, shikonin being a naphthoquinone (55). This response may indicate a functional independence of the two compounds on cell proliferation.…”
Section: Combinatorial Analysis Of Cell Lines Treated With Z285 Andmentioning
confidence: 82%
“…MDA-MB-231 demonstrated an antagonistic response with the compound combination. Lin et al, also observed some antagonistic responses when treating this cell line with shikonin and 4-OHT, shikonin being a naphthoquinone (55). This response may indicate a functional independence of the two compounds on cell proliferation.…”
Section: Combinatorial Analysis Of Cell Lines Treated With Z285 Andmentioning
confidence: 82%
“…Several reports described that SHI induced apoptosis [ 15 ] in colon cancer cell lines [ 63 ], pancreatic cancer [ 64 ], and non-small cell lung bronchial carcinoma tumor cells [ 65 ]. Inhibition of proliferation in breast cancer cell lines has also been attributed to apoptosis induction [ 66 ], and in colorectal cancer cells, administration of SHI increased ROS levels, which in turn induced intrinsic apoptosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that cancer cells are characterized by uncontrolled cell proliferation and decreased apoptosis [ 30 , 31 ]. In this research, we found that OIP5-AS1 knockdown significantly suppressed the colony formation, proliferation, and cell cycle progression in vitro .…”
Section: Discussionmentioning
confidence: 99%